Ameloblastoma: A Common Benign Odontogenic Tumour with Multiple Manifestations - Satya Ranjan Misra (Indian Journal of Forensic Medicine & Toxicology, 2020)
A myriad of odontogenic cysts and tumours both benign and malignant are seen in the maxilla and themandible. One of the most frequently encountered odontogenic tumour is ameloblastoma and has differentclinical and histologic variants which dictate the treatment plan. It has a properly documented inclinationtowards a local infiltration and tendency of recurrence. Ameloblastoma is a benign intraosseous odontogenicepithelial tumour which is locally invasive and locally destructive, non-functional, intermittent in growth,anatomically benign and clinically persistent. The tumour arises from the epithelial cell rest of malassez,from the walls of odontogenic cyst and from the basal cells.